2005
DOI: 10.1557/jmr.2005.0171
|View full text |Cite
|
Sign up to set email alerts
|

Platelet interlocks are the key to toughness and strength in nacre

Abstract: Nacre, the inner layer of mollusk shells is a composite made of platelets of mineral aragonitic calcium carbonate with a few weight percent organic material sandwiched in between. The organic and nanostructural nuances are often suggested to be the reason for the extreme toughness of nacre. Here we report the presence of interlocks between platelets of nacre from red abalone. We also report and show, using three-dimensional finite element modeling, that interlocks are the key mechanism for the high toughness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(118 citation statements)
references
References 8 publications
4
112
0
2
Order By: Relevance
“…Song et al [24,25] found the mineral bridges (which are mineral connections crossing a protein layer between adjacent mineral platelets) and proposed a "Brick, Bridge, and Mortar" model to interpret the strengthening mechanism of nacre structures. Katti et al [26] developed a platelet interlock model. Barthelat et al [27] observed a wavy structure and presented an FE model.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [24,25] found the mineral bridges (which are mineral connections crossing a protein layer between adjacent mineral platelets) and proposed a "Brick, Bridge, and Mortar" model to interpret the strengthening mechanism of nacre structures. Katti et al [26] developed a platelet interlock model. Barthelat et al [27] observed a wavy structure and presented an FE model.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them only mention the qualitative phenomena with little discussion of quantitative findings and reference to macroscopic behavior. Recent works confirm that the main mechanism contributing to significant toughening of nacre is energy-dissipating sliding of the platelets at the submicrometer scale [73,74,83]. Nano-order mechanisms are, however, important in controlling the platelet sliding behavior.…”
Section: Toughening Mechanismmentioning
confidence: 99%
“…Several origins of the interlocking and frictional resistance have been reported (figure 5), including nanoasperity on the platelet surface [8,9,80], mineral bridging [38,[80][81][82][83] and waviness of the platelet [73,80,83,84]. Nanoasperity and mineral bridging may be effective at the initial interlocking and may also generate some frictional resistance during the sliding.…”
Section: Deformation Behaviormentioning
confidence: 99%
“…18 The aforementioned micromechanical approaches can be relatively straightforwardly extended to the realm of microporomechanics, 19 considering also the effect of fl uids fi lling different pore spaces, such as the intermolecular, the intercrystalline, the lacunar, and the vascular spaces in bone. 20 , 21 This also opens the hierarchical approaches described here to the coupled biochemo-mechanical analyses described in the previous section.…”
Section: Hierarchical Approachesmentioning
confidence: 99%